FINDING COMMON GROUND: Balancing Muslim Burial Practices And State Law in Göttingen - Ahmad Bunyan Wahib (AL-TAHRIR, 2022)
This article discusses the burial practices of Muslims in Göttingen, Germany. Differences between Islamic law and German state law, both procedurally and substantively, have created problems for German Muslims in carrying out burials. Based on interviews with two respondents who have experience in caring for the deceased, the article argues that the burial process involves elements of both the implementation and neglect of Islamic law. Islamic law is evident in the process of bathing, shrouding, and offering funeral prayers for the deceased. However, during the waiting period between a person's death and burial, as well as during the burial process itself, the respondents leave Islamic law behind and follow the laws of the state. This approach is influenced by two factors: if the times for implementing both laws do not overlap, then German Muslims can apply Islamic law. However, if the times for implementing both legal systems overlap, German Muslims choose to follow state law. Additionally, during the burial process, German Muslims cannot fully implement Islamic law due to limited burial facilities. The limited cemetery space for Muslims prevents them from burying the deceased facing Mecca.